MANAJEMEN RISIKO KESELAMATAN DAN KESEHATAN KERJA DENGAN METODE HIRARC PADA PROYEK PT X TAHUN 2022 - Arafah Fadilah, (2022)
HIRARC (Hazard Identification, Risk Assessment and Risk Control) is a method that is carried out with the start of planning, hazard identification, determining risks, to the determination of various control measures. This study was conducted to identify hazard, risk assessment, and provide risk control recommendations with the HIRARC method on PT X Project. This study was conducted using qualitative research types. The study begins with the classification of activities contained in the PT X Project which is then carried out hazard identification in each work so that the source of danger will be assessed using risk assessment with the HIRARC method. Based on the research, as many as 8 sequences of structural work have been obtained, divided into 3 types of work, namely reinforcing work, formwork, and casting. Based on the work of the structure has been found as many as 62 sources of danger, namely 15 sources of danger with high risk (24%), 31 sources of danger with medium risk (50%), and 16 sources of danger with low risk (26%). It can be concluded that the risks contained in the PT X Project are dominated by medium to high-level risks. So that control recommendations are obtained in accordance with the control hierarchy, namely elimination, substitution, engineering control, control administration, and PPE.